2003
DOI: 10.1086/376506
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Combinations of Recombinant Subtype E and B Human Immunodeficiency Virus Type 1 Envelope Glycoprotein 120 Vaccines in Healthy Thai Adults

Abstract: Safety and immunogenicity of 2 recombinant human immunodeficiency virus (HIV) type 1 envelope glycoprotein (gp) 120 vaccines derived from SF2 (subtype B) and CM235 (CRF01_AE, Thai E) were evaluated in 370 Thai adults at low risk of HIV infection. Various doses of CM235 (25, 50, or 100 microg) and SF2 (0, 25, or 50 microg) gp120 were used. Eighty volunteers received placebo. There were no serious adverse events related to vaccination. Binding antibody developed in all vaccine recipients. There was no dose respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 30 publications
3
52
0
Order By: Relevance
“…In this regard, it may be too optimistic to expect that the isolate-based candidate vaccines (currently in phase II and III human clinical trials) could be cross-reactive enough to protect against circulating viruses. Thus, using a central antigen such as COT might contribute to improvements over isolate-based vaccine approaches (26). Although more studies are necessary to determine whether central sequences will elicit cross-reactive responses sufficient to be protective, recent studies with a second-generation CON group M env vaccine showed that it elicited improved levels of neutralizing antibodies in guinea pigs, in some cases stronger and broader than those of contemporary isolates (19).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it may be too optimistic to expect that the isolate-based candidate vaccines (currently in phase II and III human clinical trials) could be cross-reactive enough to protect against circulating viruses. Thus, using a central antigen such as COT might contribute to improvements over isolate-based vaccine approaches (26). Although more studies are necessary to determine whether central sequences will elicit cross-reactive responses sufficient to be protective, recent studies with a second-generation CON group M env vaccine showed that it elicited improved levels of neutralizing antibodies in guinea pigs, in some cases stronger and broader than those of contemporary isolates (19).…”
Section: Discussionmentioning
confidence: 99%
“…Since neutralizing antibodies against these epitopes do not appear to constitute a significant fraction of the plasma response against Env generated during HIV-1 infection or by vaccination, their epitopes appear to be poorly immunogenic (18). Typically, immune sera from vaccine trials to date at best neutralize only the matched vaccine strain and a few neutralization-sensitive primary isolates (30,32,111,141).…”
mentioning
confidence: 99%
“…First, and the approach followed in current clinical trials, is to choose one or a small number of laboratory-grown or primary viral isolates, typically chosen to approximate a "circulating" strain or to simply match the HIV-1 subtype(s) in the targeted population (16,18,24,52). An advantage of this approach is that it typically employs viral genes derived from a viable virus and thus produces antigens likely to adopt "native" conformations.…”
mentioning
confidence: 99%